Grain size statistics and morphometric analysis of Kluang-Niyor, Layang-Layang, and Kampung Durian Chondong Tertiary Sediments, Onshore Peninsular Malaysia: Implications for paleoenvironment and depositional processes - Sani Ado Kasim; Mohd Suhaili Ismail; Nisar Ahmed (Journal of King Saud University: Science, 2023)
Grain size statistics, morphometric and petrographic analyses of sediments and pebbles from the Tertiary sedimentary basins in Johor, onshore Peninsular Malaysia were carried out and presented in this article. The objective of the study was to interpret the depositional processes and paleoenvironment of the Tertiary sediments in the Kluang-Niyor, Layang-Layang, and Kampung Durian Chondong basins. Petrographic analysis reveals that the sandstones are mainly arenites and subfeldspathic arenites, based on the relative proportions of quartz, feldspar and lithic fragments. The textural immaturity of the sandstones suggests that the sediments were transported from a close source, and deposited along a passive continental margin. Grain size results indicate that the mean, standard deviation (sorting), skewness and kurtosis values for the sediment samples range from −0.57 Ф to 0.68 Ф (very coarse-grained to coarse-grained sandstones); 1.35 Φ to 2.27 Φ (indicating poorly sorted to very poorly sorted sandstones); 0.00 Ф to 0.36Ф (nearly symmetrical, finely skewed to strongly fine skewed); and 0.71Φ to 1.32Φ (platykurtic, mesokurtic to leptokurtic), respectively. The predominance of very coarse to coarse-grained sediments suggests low energy conditions of deposition and the poor sorting is the result of rapid deposition by strong, fluctuating currents. This, in conjunction with the various bivariate plots employed, including the Linear Discriminant Analysis (LDA) diagrams, has aided in discriminating fluvial from other depositional environments. Using Passega’s diagram, the C-M pattern of these Tertiary sediments indicated that they were transported by rolling and bottom suspension. Moreso, pebble morphometric results show the mean values of the various morphometric parameters as follows: flatness ratio (S/L = 0.49), elongation ratio (I/L = 0.73), maximum projection sphericity (ΨP = 0.69), Oblate-Prolate index (OPI = 0.45), and roundness (50.526). The pebbles of these basins were shaped in a river environment, based on measured and computed morphometric indices. Results of granulometric statistics, morphometric indices and petrography together with bivariate plots, as well as the absence of fossils/trace fossils suggest that these isolated Tertiary basins’ sediments were transported by rolling and bottom suspension (a very short distance of transport), deposited by a high-energy fluvial depositional system, close to the source.